2010
DOI: 10.1289/ehp.0901561
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Low-Level Lead Exposure and Fetal Growth

Abstract: BackgroundLimited epidemiologic studies have examined the association between maternal low-level lead exposure [blood lead (PbB) < 10 μg/dL] and fetal growth.ObjectiveWe examined whether maternal low-level lead exposure is associated with decreased fetal growth.MethodsWe linked New York State Heavy Metals Registry records of women who had PbB measurements with birth certificates to identify 43,288 mother–infant pairs in upstate New York in a retrospective cohort study from 2003 through 2005. We used multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
128
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 26 publications
5
128
4
3
Order By: Relevance
“…26 Maternal lead exposure during pregnancy was reported to negatively affect gestational length and to increase the risk of preterm and small-for-gestational age infants. 1,11,12,14,25,27 However, in these studies, the lead levels in maternal blood were .5 mg/dL, thus the effects of the very low levels currently observed in developed countries are still to be thoroughly evaluated. In addition, environmental constraints on fetal growth may not only affect birth outcomes, but also have lasting effects on postnatal growth.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…26 Maternal lead exposure during pregnancy was reported to negatively affect gestational length and to increase the risk of preterm and small-for-gestational age infants. 1,11,12,14,25,27 However, in these studies, the lead levels in maternal blood were .5 mg/dL, thus the effects of the very low levels currently observed in developed countries are still to be thoroughly evaluated. In addition, environmental constraints on fetal growth may not only affect birth outcomes, but also have lasting effects on postnatal growth.…”
Section: Discussionmentioning
confidence: 98%
“…However, low-level exposure to lead still continues because of the widespread use of lead and its persistent nature. 1,2 The mean blood lead level among childbearing women in the United States was 1.2 mg/dL according to the national survey conducted in [2003][2004], and the level in childbearing Korean women was 1.6 mg/dL by the national survey conducted in 2008-2009. 3,4 Exposure to low-level lead is known to induce a wide range of adverse health effects, 5 and children are particularly sensitive to its effects because of the ongoing development of body organs and the nervous system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a large cohort involving more than 34 000 live births, investigators found that a 5-μg/dL (50-ppb) increase in blood lead concentrations was associated with a 61-g decrement in birth weight. 26 The National Toxicology Program concluded that maternal blood lead concentrations <5 μg/dL (<50 ppb) are associated with lower birth weight.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Hg exposure occurs in the daily intake of rice in China [6]. Prenatal exposure to environmental chemicals such as organophosphate insecticides, tobacco smoke, heavy metals and perfluorinated compounds (PFCs) is associated with fetal growth restriction and low birth weight of infants [7][8][9][10]. The concentration of chemicals detected in the fetal environment is, however, relatively low (around 0.1-10 ppb level) and far from the levels reported in pharmacological studies.…”
mentioning
confidence: 99%